Increasing MSME Revenues in Lalepo Village, Kahu District, Bone: The Impact of Public Business Loans (KUR) from BRI Unit Palattae - Alamsjah; Zalkha Soraya; Murniati; Muslim Nursalam Akhmad (Jurnal Manajemen Bisnis, 2023)
This study investigates the impact of People's Business Credit (KUR) provided by BRI Palattae Unit on the income growth among MSMEs in Lalepo Village, Kahu District, Bone Regency. The research was conducted over two months, from April to May 2022, within the confines of Lalepo Village. The research approach is quantitative, aligned with the positivist philosophy, which seeks to examine a specific population or sample to test predetermined hypotheses. This quantitative research employed a multiple linear regression model, and data analysis was conducted using the SPSS v25.0 application for Windows. The t-test results (partial) revealed a t-count value of 3.801, surpassing the t-table value of 2.014 at a significance level of 0.000. As the t-count value exceeds the t-table value with significance less than 0.05, the findings of this study confirm a positive and statistically significant influence of People's Business Credit (KUR) from Bank Rakyat Indonesia Palattae Unit, contributing to a 21.5 percent increase in the income of SMEs in Lalepo Village, Kahu District, Bone Regency. The remaining 78.5 percent of income variation is attributed to other unexamined variables.